Botrychium simplex E. Hitchc. (Ophioglossaceae) – a new species for the native flora of Ukraine - Parnikoza, Ivan Yu.; Celka, Zbigniew (Biodiversity: Research and Conservation, 2016)
The work presents the results of herbarium survey that resulted in finding Botrychium simplex E. Hitchc. – a new for the native Ukrainian flora species of the family Ophioglossaceae. A specimen of this taxon was found in the National Herbarium of Ukraine in the M. G. Kholodny Institute of Botany of National Academy of Sciences of Ukraine in Kyiv (KW) among the specimens of Botrychium lunaria (L.) Sw. originating from the surroundings of Kharkiv. Thus, this finding indicates the most south-eastern locality of B. simplex in Europe found so far.